2021
DOI: 10.1088/1757-899x/1114/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of flow pattern around series of groynes with different orientations in meandering channels

Abstract: The mechanism of flow and turbulence around groynes in a meandering channel is very complex phenomena. To simulate the flow pattern around groynes in meanders a 3D numerical model was built with groynes of different inclinations by using ANSYS Fluent. The developed model was verified by the results of experimental study in meanders. Pressure, velocity, stream lines and turbulent kinetic energy for different groyne angles such as 15°, 30°, 45°, 90°, 120° and 150° were compared and analyzed to find the ideal ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…By considering the most critical parameters, such as the relative radius and the bridge pier position, they demonstrated that their model was able to not only approximate but also foresee the maximum scour and sedimentation [28]. Indulekha et al (2021) modeled the flow pattern around groynes in meandering paths by developing a 3D numerical model with varied inclinations of groynes. The results referred to the efficiency of the model to study flow and turbulence regarding groynes in meanders [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By considering the most critical parameters, such as the relative radius and the bridge pier position, they demonstrated that their model was able to not only approximate but also foresee the maximum scour and sedimentation [28]. Indulekha et al (2021) modeled the flow pattern around groynes in meandering paths by developing a 3D numerical model with varied inclinations of groynes. The results referred to the efficiency of the model to study flow and turbulence regarding groynes in meanders [29].…”
Section: Introductionmentioning
confidence: 99%
“…Indulekha et al (2021) modeled the flow pattern around groynes in meandering paths by developing a 3D numerical model with varied inclinations of groynes. The results referred to the efficiency of the model to study flow and turbulence regarding groynes in meanders [29]. Das et al (2022) studied boundary shear stress in non-prismatic compound channel considering the relative flow depth and divergence angle.…”
Section: Introductionmentioning
confidence: 99%